(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe characteristics of depressive disorders in patients with chronic hepatitis B treated at Bach Mai Institute of Tropical Medicine, Bach Mai Hospital in 2025-2026. Subjects and methods: A cross-sectional descriptive study on 257 patients diagnosed with chronic hepatitis B treated at the Bach Mai Institute of Tropical Medicine from December 2025 to March 2026. Results: The prevalence of depressive disorders in patients with chronic hepatitis B was 20.2%, of which 15.2% of cases were mild, 5.1% of cases were moderate, and no cases of severe depression were recorded. For typical symptoms, 100% of depressed patients exhibited reduced energy leading to increased fatiguability and 88.5% had depressed mood. Common symptoms that predominated included disturbed sleep (94.2%), diminished appetite (82.7%), and reduced concentration and attention (75%). In terms of somatic symptoms, most of patients experience waking in the morning 2 hours or more before the usual time (88.5%), marked loss of appetite (82.7%) and marked loss of interest or pleasure in activities that are normally pleasurable (78.8%). There were no recorded cases of self-injury or suicidal thoughts or behaviors. Conclusion: Depressive disorders are common in patients with chronic hepatitis B treated at the Bach Mai Institute of Tropical Medicine, mostly occurring at mild to moderate severity. The somatic symptoms of depression are characterized by disturbed sleep and diminished appetite, creating a pronounced symptom overlap with the manifestation of liver disease.